The Relationship Between Family Knowledge and Relapse Among Schizophrenia Patients at the Psychiatric Clinic of TK II Robert Wolter Mongisidi Hospital, Manado - Agus Prayitno; Noifke Kaghoo; Stendy Ali (Nursing Care Journal, 2025)
Background: Schizophrenia is a chronic mental disorder characterized by disturbances in thought, perception, and behavior. One of the major challenges in managing schizophrenia is the high rate of relapse, which is often influenced by the family’s level of knowledge and ability to provide home care. Objective: This study aimed to determine the relationship between family knowledge and relapse among schizophrenia patients at the Psychiatric Clinic of Tk II Robert Wolter Mongisidi Hospital, Manado.Methods: This research used a quantitative analytical design with a cross-sectional approach. A total of 89 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test.Results: The findings showed that most families (76.4%) had poor knowledge, and most patients (79.8%) experienced relapse. The Chi-Square test revealed a significant relationship between family knowledge and relapse among schizophrenia patients (p = 0.000, p < 0.05). Conclusion: There is a significant correlation between family knowledge and relapse among schizophrenia patients. Families with better understanding of schizophrenia are more capable of providing effective care and preventing relapse. Continuous education and family empowerment are essential to improve patient outcomes and reduce relapse rates.